Analisis Models Of TOC: Studi Kasus Cyber Crime oleh Philippines Offshore Gaming Operator Filipina (2016-2024) - Muhammad Farhan; Angelique Kishiola Prima Foraihmbrasi; Daniel Raka Putra Leofranz; Danish Mustaghfirin Ihyawijaya; Angelina Ruslie (Department of International Relations, Brawijaya University, 2026)
This article discusses Transnational Organized Crime, specifically Philippine Offshore Gaming Operators (POGOs), during the period 2016–2024. The objective is to analyze the application of transnational crime anticipation models in the context of POGOs and cybercrime. Methodologically, this study employs Cockayne’s activity-based approach and the Models of TOC by Williams and Godson, focusing on the political model and the hybrid or composite model. Data was drawn from official government reports, Senate investigations, and other literature. The key finding is that the POGO ecosystem functions as a shadow economic infrastructure rather than an instrument of formal economic development. In the political model, weak regulation by the Philippine Amusement and Gaming Corporation (PAGCOR) and corruption among local officials allow criminal syndicates to operate safely without fear of law enforcement. In the hybrid or composite model, these networks thrive by exploiting legal loopholes, using cryptocurrency money laundering, and engaging in human trafficking for forced labor. Ultimately, the total ban on POGOs in 2024 demonstrates that stopping transnational cybercrime syndicates depends entirely on strong political will and decisive government action.